2016
DOI: 10.1182/blood-2015-09-671040
|View full text |Cite
|
Sign up to set email alerts
|

Haploinsufficiency for NR3C1, the gene encoding the glucocorticoid receptor, in blastic plasmacytoid dendritic cell neoplasms

Abstract: Key Points• NR3C1 haploinsufficiency is found in patients with a plasmacytoid dendritic cell neoplasm characterized by very poor clinical outcome.• Overexpression of lincRNA3q is a consistent feature of malignant cells in these patients and can be abrogated by BET protein inhibition.Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a rare and highly aggressive leukemia for which knowledge on disease mechanisms and effective therapies are currently lacking. Only a handful of recurring genetic mutations ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 69 publications
(93 reference statements)
4
30
0
Order By: Relevance
“…We found that genes silenced by PRC2 (EZH2) were the most overrepresented in the group of up‐regulated genes in BPDCN. This agrees with a previous report of a loss‐of‐EZH2 expression signature in tumor cells from patients with highly aggressive BPDCN . Remarkably, it has been established that IKZF1, which predominantly acts as a transcriptional repressor, silences genes in erythroid and T‐cell precursors by recruiting PRC2 to target sites .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that genes silenced by PRC2 (EZH2) were the most overrepresented in the group of up‐regulated genes in BPDCN. This agrees with a previous report of a loss‐of‐EZH2 expression signature in tumor cells from patients with highly aggressive BPDCN . Remarkably, it has been established that IKZF1, which predominantly acts as a transcriptional repressor, silences genes in erythroid and T‐cell precursors by recruiting PRC2 to target sites .…”
Section: Discussionsupporting
confidence: 92%
“…BPDCN, blastic plasmacytoid dendritic cell neoplasm; CPC, chromosomal passenger complex; NDC80, NDC80 kinetochore complex [Color figure can be viewed at wileyonlinelibrary.com] with a previous report of a loss-of-EZH2 expression signature in tumor cells from patients with highly aggressive BPDCN. 54 Remarkably, it has been established that IKZF1, which predominantly acts as a transcriptional repressor, silences genes in erythroid and T-cell precursors by recruiting PRC2 to target sites. 55,56 Thus, up-regulation of genes silenced by PRC2 in BPDCN might result from shortage of functional IKZF1 molecules, which in turn, would hinder PRC2 recruitment to target sites.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies indicate that BET inhibition is an attractive therapeutic strategy in hematological and solid cancers. Single or dual agent therapy is showing promise pre-clinically [ 1 , 3 , 6 , 31 , 32 ]. Inhibitors are mostly small molecule inhibitors that are thought to mediate anti-cancer activity through the interruption of interactions between BET proteins and acetylated lysine in histones at promoters and enhancers.…”
Section: Bet Inhibition As An Anti-cancer Therapy and Perspectivesmentioning
confidence: 99%
“…7 The pathobiology of BPDCN is poorly understood and the number of reports exploring its molecular features is still limited. 821 Recent advances in the understanding of the BPDCN molecular landscape have paved the way for novel treatment approaches based on the inhibition of the BCL2 protein, 22 the activation of the cholesterol efflux, 23 the repression of the Bromodomain-containing protein 4 (BRD4), 24 and binding to the interleukin-3 receptor (IL3R). 25 All these potential therapeutic options (which are worthy of further evaluation) have mainly emerged from the analysis of the BPDCN transcriptome or from its antigenic repertoire.…”
Section: Introductionmentioning
confidence: 99%